Prevalence of comorbidities and secondary health conditions among the Finnish population with spinal cord injury - Tallqvist, Susanna; Kauppila, Anna-Maija; Vainionpää, Aki; Koskinen, Eerika; Bergman, Paula; Anttila, Heidi; Hämäläinen, Harri; Täckman, Anni; Kallinen, Mauri; Arokoski, Jari; Hiekkala, Sinikka (Spinal cord, 2022)
Study designA cross-sectional study.ObjectivesTo explore the prevalence of comorbidities, secondary health conditions (SHCs), and multimorbidity in the Finnish population with spinal cord injury (SCI).SettingThe data were collected from the Finnish Spinal Cord Injury Study (FinSCI). Participants were identified from three SCI outpatient clinics responsible for the lifelong follow-up of persons with SCI in Finland, (n = 884 participants, response rate; 50%).MethodsThe FinSCI-questionnaire included a question from the National Study of Health, Well-being, and Service (FinSote) for screening 12 comorbidities. The reference data of the general population for that question were received from the Finnish Institute for Health and Welfare. The Spinal Cord Injury Secondary Condition Scale (SCI-SCS) was used to screen 16 SHCs. The data were analysed with univariate testing and multivariable negative binomial regression modelling.ResultsThe most common comorbidities were high blood pressure/hypertension (38%), back problems (28%), and high cholesterol (22%). The most common SHCs were joint and muscle pain (81%), muscle spasms (74%), chronic pain (71%), and bowel problems (71%). The prevalence of comorbidities was highest among persons aged ≥76 years (mean; 2.0; scale range; 0–12). The prevalence of SHCs was highest in the severity of SCI group C1–4 AIS A, B, and C (mean; 8.9; scale range; 0–16).ConclusionsFurther research on geriatrics in SCI, non-traumatic SCI, and knowledge of the needs of persons with cervical lesion AIS A, B, or C is required, due to the fact that the prevalence of multimorbidity is high in these groups.